Evaluación técnica y financiera de la implementación de un hidrociclón que permita el mejoramiento de la separación agua-aceite en superficie, para mejor disposición, control y tratamiento del agua en campo Caño Sur (2019)
For the development of this project, simulations were carried out with two specialized software’s (PROSPER and WELLCAT), through which nodal analyses and analysis of efforts for completion were carried out, This is in order to identify the optimal operating conditions for a correct hydrocyclone installation in the field. Subsequently, a detailed description of the operations to be carried out, in which the conversion of a producing well to an injector is taken into account, with their respective times and steps to follow. Finally, a financial analysis is carried out, which aims to identify the viability of the project. This is developed by means of a flow chart of discharge, obtaining at the end a differential of the VPN values for the current processes, that is the installation of the facilities of production and treatment of water, and the case raised in this project, the installation of the hydrocyclone, resulting in low operating costs to a projection of ten years.